Appropriateness in the Utilization of Emergency Department Services In Hospital Kota Sharu and Hospital Universiti Sains Malaysia - Naing, Lin; Hj. Mohd Sadiq, Mohd Ayub; Hj Ghazali, Dr Selasawati (Universiti Sains Malaysia, 2000)
The prime concern in the inappropriate utilization of emergency departments (FD) is compromised management of patients requiring emergency treatment.